Local and regional experiences with assessing and fostering ocean health. (September 2016) - Blasiak, Robert; Pacheco, Erich; Furuya, Ken; Golden, Christopher D.; Jauharee, Ahmed Riyaz; Natori, Yoji; Saito, Hiroaki; Sinan, Hussein; Tanaka, Takehiro; Yagi, Nobuyuki; Yiu, Evonne
Abstract: During the international symposium on "Regional Applications and Nexus of the Ocean Health Index" at The University of Tokyo in Japan in July 2015, a range of experts, practitioners and researchers discussed the potential for assessing the current state of ocean health at different scales, as well as changes over time. Discussions focused on how the successful assessment and implementation of projects aimed at fostering ocean health and resilient coastal ecosystems strongly depends on a multi-stakeholder approach and local leadership. In addition, recent examples of regional independent assessments conducted using the Ocean Health Index were introduced, with an accompanying explanation of how the Index goals can be adjusted, specified or weighted in line with a local context or policy direction. This manuscript introduces key points raised during the symposium as well as relevant supplementary materials. Highlights: Multi-stakeholder approaches crucial for regional ocean projects/assessments. Social and ecological aspects of marine systems must both be considered. Innovative methods needed to supplement national datasets with detailed local data. Local leaders crucial for ensuring successful activities and building social capital.